Cooperative Effects in Chemistry—Collaborative Research Center SFB 858 in Münster. Issue 25 (23rd February 2017) - Tebben, Ludger; Studer, Armido
Abstract : Cooperative effects are found in various research areas in chemistry, many of which are currently explored within the Collaborative Research Center SFB 858 in Münster. This Editorial gives some insights into the field and an overview of the history of the Center and those who have contributed to the development of this fascinating multidisciplinary research area.